Il comentum di Benvenuto da Imola e gli ungheresi - Szörényi, László (Verbum – Analecta Neolatina, 2002)
The Author provides a survey on the presence of references to Hungary and Hungarians in Benvenuto da Imola’s commentary on Dante’s work. These references were used until now as indications for the dating - Szörényi shows several elements that refer to Louis I, the Great’s military campain against Naples. Of course, Benvenuto’s information about Hungary does not seem very rich.